Optimisation des techniques culturales pour l’amélioration des rendements de la pomme du terre de consommation - BENMESSAOUD, Abderrahmane; MEZIANE BENTAHAR MEZIANE, Omar (My University, 2021)
The cultivation of potatoes is a promising crop which offers many advantages; From an agronomic point of view, its cultivation is easy, its yield potential is high (20 to 30 t / ha). From a nutritional point of view, it ranks among the most nutritious tuber plants with a high energy content. From a commercial point of view, it is highly regarded by the people and is a cash crop for many farmers. It plays a key role in the global food system, It is the main non-grain food commodity in the world and world production reached a record 329 million tonnes in 2009 (FAO, 2010). In developed countries, potato consumption is increasing dramatically and represents more than half of the world harvest. Because it is easy to grow and has a high energy content, it is a valuable cash crop for millions of farmers.